Teaching Arabic as a Second Language in International School in Dubai A case study exploring new perspectives in learning materials design and development - Sakho, Mohamed Lemine (2012)
Teaching Arabic as Second/Foreign Language (TASL/TAFL) is still, in many parts of the world, based on intuition and unprincipled methods. Many textbooks and materials designed for this purposes still use outdated pedagogy in Second Language teaching. Although there are some attempts to break with this negative tradition, this gap is still noticed. Since TASL/TAFL has become a global educational enterprise, there is need for sound academic research to be conducted in order to inform the profession. This study investigates ways in which teachers of Arabic as Second Language can be helped to design and develop their own teaching materials. It makes a brief review of theories and principles which are considered in designing syllabuses of other languages, mainly English, for non native learners, and shows how such theories and principles can be adapted in designing Arabic learning materials for non Arabs. The study focuses on international schools in Dubai with the assumption that conclusions reached may be adaptable in other similar context, offering insight on key issues of syllabus design, such as selection.